INFORMATION ASPECT OF COORDINATION OF PRODUCTION PROCESSES - YUKHIMCHUK, Mariia; DUBOVOI, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Production systems with multi-zone technological facilities together with technological process management tools belong to the class of cyber-physical systems. The combination of three aspects: the presence of physical interactions in a distributed technological object, the presence of complex local control scenarios that depend on the state parameters of the object area, decentralization and the presence of global criteria led to a new class of tasks - spatio-temporal coordination of systems with continuous technological objects objects and logical management. The purpose of the research is to increase the effectiveness of decentralized coordination due to the optimization of information flows and the structure of coordination subsystems. The relationship between the amount of information regarding the state of production processes and the uncertainty of coordination of related operations is considered. The dispersion of the state of the object element was estimated using the spatio-temporal spectrum of the state. Checking the adequacy of information flow estimates and its dependence on system parameters was performed using experiments on a simulation model on the Scilab platform. The values of information flows obtained as a result of statistical processing of data from simulation experiments according to Shannon's measure differed from the calculated values by 18%. Considering packet data transmission, this does not affect the overall estimate of the required bandwidth of the data transmission system. The proposed approach to the assessment of information flows in the system of decentralized coordination can be used to select the parameters of the data transmission system, as well as to optimize the structure and information flows of the coordination system.
Keywords: decentralized coordination; information; parameter uncertainty